2000
DOI: 10.1159/000054578
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of the Hypothalamic-Pituitary-Adrenal Response to Stress

Abstract: Pathological consequences of stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis may be related to the duration rather than to the intensity of HPA axis activation after exposure to the stressor. Consequently a fine analysis of post-stress events is of importance. The present experiments were designed to study the importance of three key factors in HPA recovery: intensity of the stressor (experiment 1), duration of exposure to the stressor (experiment 2) and previous experience of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(43 citation statements)
references
References 53 publications
3
40
0
Order By: Relevance
“…Immobilization is known to be a severe stressor accompanied by a pronounced ACTH (corticotropin) response (42). Our finding that comparatively mild emotional stress such as elevated platform exposure was sufficient to trigger the release of SP in the MeA contributes to a growing literature that SP functions as a stress neurotransmitter͞neuromodulator in the CNS.…”
Section: Discussionmentioning
confidence: 55%
“…Immobilization is known to be a severe stressor accompanied by a pronounced ACTH (corticotropin) response (42). Our finding that comparatively mild emotional stress such as elevated platform exposure was sufficient to trigger the release of SP in the MeA contributes to a growing literature that SP functions as a stress neurotransmitter͞neuromodulator in the CNS.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, chronic immobilization stress induces a decrease in ACTH elevation, measured immediately after the stress, and a faster return to basal levels. This faster return to basal levels is also displayed by corticosterone [30]. In addition, Bauer et al [31] report that after acute restraint stress, rats display a significant increase in plasma corticosterone and a suppression of peripheral blood lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 92%
“…In view of the new insights in the involvement of the hippocampus and brain cortex in the regulation of stress response [1][2][3][17][18][19] and the well established molecular mechanism by which glucocorticoids accomplish their function via glucocorticoid receptor (GR) and GR-associated proteins [5,[9][10][11][12][14][15][16], it was of interest to determine the changes in hippocampal and cortical GR and Hsp 70 after various stressors applied in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that animals chronically exposed to a particular stressor display an exaggerated response of the limbic-hypothalamo-pituitary adrenal (LHPA) axis to various novel stressors, as judged by the plasma level of glucocorticoids and ACTH [17][18][19]. In addition to that, a number of data indicated that apart from the hippocampus, chronic stress may also affect the brain cortex [20][21][22].…”
Section: Introductionmentioning
confidence: 99%